1994
DOI: 10.1073/pnas.91.15.7071
|View full text |Cite
|
Sign up to set email alerts
|

Cell-surface receptors for gibbon ape leukemia virus and amphotropic murine retrovirus are inducible sodium-dependent phosphate symporters.

Abstract: Cell surface receptors for gibbon ape leukemia virus (Glvr-1) and marine amphotropic retrovirus (Ram-i) Ram-i (10) and human Glvr-1 (7) cDNAs were cloned into pGEM-7Z (Promega) with their 5' ends adjacent to the SP6 promoter. For mRNA synthesis, the plasmids were linearized and transcribed with SP6 polymerase in the presence of m7G(5')ppp(5')G caps according to the manufacturer's directions (Pharmacia). Xenopus laevis oocytes were injected with 50 nl of mRNA (1 ng/nl) or with an equal volume of H20 and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
464
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 568 publications
(483 citation statements)
references
References 45 publications
18
464
1
Order By: Relevance
“…Previous studies showed that the Ampho receptor Pit2 should be highly expressed in liver tissue, but the exact cell types of expression were not delineated. 36 Published reports have shown that retroviral vectors carrying the amphotropic envelope can transduce hepatocytes, but in most circumstances liver proliferation has been induced to overcome the cell cycle requirement of these vectors; so the transduction patterns are not entirely dependent on the envelope. 37,38 Thus, this study is the first reported use of Amphopseudotyped lentiviral vectors in vivo, and demonstrates the transduction of mouse hepatocytes in the absence of any liver proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the Ampho receptor Pit2 should be highly expressed in liver tissue, but the exact cell types of expression were not delineated. 36 Published reports have shown that retroviral vectors carrying the amphotropic envelope can transduce hepatocytes, but in most circumstances liver proliferation has been induced to overcome the cell cycle requirement of these vectors; so the transduction patterns are not entirely dependent on the envelope. 37,38 Thus, this study is the first reported use of Amphopseudotyped lentiviral vectors in vivo, and demonstrates the transduction of mouse hepatocytes in the absence of any liver proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…RD envelope protein shares the common cell-surface receptor as HERV-W, 19,20 while GALV enter cells after binding with type-III sodium-dependent phosphate transporters PiT-1. [21][22][23] It has been demonstrated that in D-and C-type mammalian retroviruses, the 16 C-terminal residues of the intracytoplasmic tail of these viruses' envelope proteins, called the 'R-peptide', inhibit their fusion activities. 24,25 Thus R-less versions of these envelope proteins were used in this study, except for the HERV-W, which does not rely on the cleavage of the R-like peptide for its fusing activity.…”
Section: Introductionmentioning
confidence: 99%
“…11,21,22 Our observed correlation between elevated progenitor transduction rates and elevated Pit2 expression in CD34-enriched marrow cells from pigtailed macaques are consistent with these studies. Whether marrow progenitors from pigtailed macaque are more susceptible to transduction with other MLV pseudotypes, such as GaLV, 11,44 is not clear.…”
Section: Figure 6 Effect Of Culture Length On Transduction Of Pigtailmentioning
confidence: 99%